Experimental investigation of Jatropha oil methyl ester (JOME) as pilot fuel with CNG in a dual fuel engine. Issue 5 (2nd September 2016) - Kumar, Parvesh; Kumar, Naveen
ABSTRACT: The increasing energy demands of fossil fuels and the environmental issues associated with their emissions have instigated research into renewable fuels. In this paper, a dual fuel was formulated using diesel with Jatropha oil methyl ester (JOME) as pilot fuel and compressed natural gas (CNG) as primary fuel in a dual fuel engine. The performance and emission characteristics of the dual fuel were compared with conventional diesel (baseline data). The mass flow rate of the primary fuel changes with load, however, the mass flow rate of the pilot fuel was kept constant for all loading conditions. Results indicate that the dual fuel engine can produce high brake thermal efficiency 32.1% and low brake specific fuel consumption 0.203 kg/kW-h as compared to baseline data at higher load. The dual fuel engine showed improvement in carbon monoxide (CO) and smoke emissions, while unburned hydrocarbons (UHC) and oxides of nitrogen (NOX ) emissions remained high. The performance and emissions characteristics for CNG–JOME mode showed better results over CNG–diesel mode at low and intermediate loads. Diesel as pilot fuel gave better results as compared to JOME as pilot fuel, at higher loads. In conclusion, JOME was a good pilot fuel for a dual fuel engine with CNG.